Understanding Giardia infections among rural communities using the one health approach - Soo, Ching Lee; Romano, Ngui; Tiong, Kai Tan; Muhammad Aidil, Roslan; Init, Ithoi; Mohammed A.K, Mahdy; Lokman, Hakim S.; Yvonne A.L., Lim (Elsevier Science, Ltd., 2017)
The epidemiology of giardiasis in rural villages in Peninsular Malaysia was examined in the context of the One Health triad that encompasses humans, animals and environment (i.e. river water). A cross-sectional study was carried out among five rural communities in Malaysia to determine the prevalence of Giardia duodenalis in humans, animals and river water. Fecal samples collected from humans and animals were examined by light microscopy. Water was sampled from the rivers adjacent to the target communities and investigated for the occurrence of Giardia cysts. The isolated cysts were further genotyped targeting the glutamate dehydrogenase and triosephosphate isomerase genes. The overall prevalence of G. duodenalis was 6.7% (18/269) and 4.7% (8/ 169) among humans and animals, respectively. Giardia cysts (mean concentration range: 0.10–5.97 cysts/L) were also found in adjacent rivers at four out of the five villages examined. At Kemensah and Kuala Pangsun, Giardia cysts were isolated from humans [rate: 3.7% each (of 54 each)], animals [rates: 6.3% (of 62) and 11.3% (of 16), respectively] and river water [average concentration of 9 samples each: 0.83 ± 0.81 and 5.97 ± 7.00, respectively]. For both villages at Pos Piah and Paya Lebar, 12.2% (of 98) and 6.1% (of 33) of collected human samples were infected, respectively whilst none of the collected animals samples in these villages were found to be positive. The river water samples of these two villages were also contaminated (average concentration: 0.20 ± 0.35 (of 9) and 0.10 ± 0.19 (of 3), respectively). In conclusion, Giardia cysts were simultaneously observed in the human-animal-environment (i.e., river water) interfaces in at least two of five studied communities highlighting a vital need to improve understanding on the interplay of transmission dynamics, the role of infected humans and animals in contaminating the water sources and the role of water as a vehicle of disease transmission in these communities. Indeed, this study illustrates the One Health approach which is to recognize that the optimal health of humans are interconnected with the well-being of animals and their environment.